Initial Experience of Challenge-Free MRI-Based Oxygen Extraction Fraction Mapping of Ischemic Stroke at Various Stages: Comparison With Perfusion and Diffusion Mapping - Zhang, Shun; Cho, Junghun; Nguyen, Thanh D.; Spincemaille, Pascal; Gupta, Ajay; Zhu, Wenzhen; Wang, Yi (Frontiers in Neuroscience, 2020)
MRI based oxygen extraction fraction imaging has great potential benefit in the selection of clinical strategies for ischemic stroke patients. This study aimed to evaluate the performance of a challenge-free oxygen extraction fraction (OEF) mapping in a cohort of acute and subacute ischemic stroke patients. Consecutive ischemic stroke patients (total 30 with 5 in acute stage, 19 in early subacute stages and 6 in late subacute stage) were recruited. All subjects underwent MRI including multiecho gradient echo (mGRE), DWI, and 3D-ASL. OEF maps were generated from mGRE phase+magnitude data which was processed using QSM+qBOLD with cluster analysis of time-evolution. CBF and ADC maps were reconstructed from 3D-ASL and DWI respectively. Further, CMRO2 was calculated as the product of CBF and OEF. OEF, CMRO2, CBF and ADC values in the ischemic cores (absolute values) and their contrasts to the contralateral regions (relative values) were evaluated. One-way analysis of variance (ANOVA) was used to compare OEF, CMRO2, CBF and ADC values and their relative values among different stroke stages. The OEF value of infarct core showed a trend of decrease from acute, to early subacute and to late subacute stages of ischemic stroke. Significant differences among the three stroke stages were only observed in the absolute OEF (F = 6.046, p = 0.005) and relative OEF (F = 5.699, p = 0.009) values of the ischemic core, but not in other measurements (absolute and relative CMRO2, CBF, ADC values, all p values > 0.05). In conclusion, the challenge-free QSM+qBOLD generated OEF mapping can be performed on stroke patients. It can provide more information of tissue viability that were not available with CBF and ADC, and thus may help to better manage ischemic stroke patients.